A phase II clinical trial of adoptive transfer of haploidentical natural killer cells for consolidation therapy of pediatric acute myeloid leukemia. Issue 1 (20th March 2019) - Nguyen, Rosa; Wu, Huiyun; Pounds, Stanley; Inaba, Hiroto; Ribeiro, Raul C.; Cullins, David; Rooney, Barbara; Bell, Teresa; Lacayo, Norman J.; Heym, Kenneth; Degar, Barbara; Schiff, Deborah; et al.
Abstract : Abstract: Consolidation therapies for children with intermediate- or high-risk acute myeloid leukemia (AML) are urgently needed to achieve higher cure rates while limiting therapy-related toxicities. We determined if adoptive transfer of natural killer (NK) cells from haploidentical killer immunoglobulin–like receptor (KIR)–human leukocyte antigen (HLA)-mismatched donors may prolong event-free survival in children with intermediate-risk AML who were in first complete remission after chemotherapy. Patients received cyclophosphamide (Day − 7), fludarabine (Days − 6 through − 2), and subcutaneous interleukin-2 (Days − 1, 1, 3, 5, 7, and 9). Purified, unmanipulated NK cells were infused on Day 0, and NK cell chimerism and phenotyping from peripheral blood were performed on Days 7, 14, 21, and 28. As primary endpoint, the event-free survival was compared to a cohort of 55 patients who completed chemotherapy and were in first complete remission but did not receive NK cells. Donor NK cell kinetics were determined as secondary endpoints. Twenty-one patients (median age at diagnosis, 6.0 years [range, 0.1–15.3 years]) received a median of 12.5 × 10 6 NK cells/kg (range, 3.6–62.2 × 10 6 cells/kg) without major side effects. All but 3 demonstrated transient engraftment with donor NK cells (median peak donor chimerism, 4% [range, 0–43%]). KIR–HLA-mismatched NK cells expanded in 17 patients (81%) and contracted in 4 (19%). However, adoptive transfer of NK cells did not decrease the cumulative incidence of relapse (0.393 [95% confidence interval: 0.182–0.599] vs. 0.35 [0.209–0.495]; P =  .556) and did not improve event-free (60.7 ± 10.9% vs. 69.1 ± 6.8%; P  = .553) or overall survival (84.2 ± 8.5% vs. 79.1 ± 6.6%; P  = .663) over chemotherapy alone. The lack of benefit may result from insufficient numbers and limited persistence of alloreactive donor NK cells but does not preclude its potential usefulness during other phases of therapy, or in combination with other immunotherapeutic agents. Trial registration: www.clinicaltrials.gov, NCT00703820 . Registered 24 June 2008.